A Few Beautiful Minutes : Experiencing a Solar Eclipse - Fox, Kate Allen; Le, Khoa, 1982- (New York : Little, Brown and Company, 2023)
"Sky gazers experience a total solar eclipse in this descriptive picture book about the wonders of this phenomenon"--
Includes bibliographical references.
Keywords: Solar eclipses -- Juvenile literature; Solar eclipses; Picture books